Gender earnings differentials in the engineering profession in Greece - Patrinos, Harry Anthony [Verfasser] (My University, 1995)
"Engineers in Greece undergo a heavy schooling investment - five years of university study instead of the usual four. Greece is atypical in that women make up a realtively large portion of the engineering work force. Working women earn substantially less than do men and there is evidence of labor market discrimination. In this paper a recent survey (1987) of employed engineers is used to examine earnings differentials between men and women and to compare the results with an examination of the results of an earlier survey (1977). Results indicate that most of the difference in earnings between male and female engineers in Greece is not accounted for by differences in productive characteristics such as education and experience and, therefore, most of the difference may be due to discrimination. Moreover, the proportion of the earnings differential not explained by productivity has increased over time. (author's abstract, IAB-Doku) ((en)) Die Ergebnisse zweier Untersuchungen in Griechenland zeigen, dass die Einkommensunterschiede zwischen weiblichen und männlichen Ingenieuren grösstenteils nicht auf Produktivitätsunterschieden aufgrund von z.B. Bildung und Berufserfahrung beruhen. Ursache für die schlechtere Bezahlung der Frauen könnte Diskriminierung sein. (IAB)
Keywords: S 6.3.1 Ingenieurberufe, Chemiker, Physiker, Mathematiker; P 1.3 Frauen; G 1.2.2.1 Lohn- & Tarifsysteme; I 2.2.1 Westeuropa; Ingenieur; Frauen in Einzelberufen; Frauenarbeit; Lohnstruktur; Berufsproblem; Geschlechtsspezifische Faktoren; Quantitative Angaben; Griechenland; 1977-1987